Model test for the simultaneous injecting of super-large rectangular pipe jacking. Issue 5 (October 2021) - Pan, Y; Li, P; Zhen, L; Li, X
Abstract: In the construction of pipe-jacking tunnels, simultaneous injecting is a key in controlling surface deformation and jacking force. At present, the traditional simultaneous injecting research is mainly limited to the study of slurry materials and the friction coefficient, while research on the flow of the slurry itself and its filling mechanism is rarely involved. By building a pipe-slurry-soil system and model test platform, this paper presents the results of a laboratory reduced-scale model test on the simultaneous injection of slurry of super-large rectangular pipe jacking. Results show that different slurries have varying effects on the quality of protective slurry screen, which contains traditional thixotropic slurry (consisting of bentonite, carboxymethyl cellulose (CMC), and soda ash) as well as HS-3 compound slurry and polyacrylamide compound slurry. Furthermore, the injection pressure, injection flowing path, and toroidal injection pressure distribution were visually and accurately measured and analyzed by installing 22 miniature soil pressure gauges on the surface of the organic glass model pipe and arranging 12 cameras inside the organic glass segment. Meanwhile, the settlement of different parts of soil and pipe-jacking force was measured to observe the influence of protective slurry screen on the ground settlement and pipe-jacking force. The injecting pressure distribution and the flow filling process of the shallow overburden large-section rectangular pipe-jacking tunnel were also explored.